Oral and intravenous pharmacokinetics of metformin with and without oral codeine intake in healthy subjects: A cross‐over study - Kuhlmann, Ida; Nøddebo Nyrup, Amanda; Bjerregaard Stage, Tore; Hougaard Christensen, Mette Marie; Korshøj Bergmann, Troels; Damkier, Per; Nielsen, Flemming; Højlund, Kurt; Brøsen, Kim (Clinical and translational science, 2021)
The aim of the study was to investigate if there is a clinically relevant drug interaction between metformin and codeine. Volunteers were randomized to receive on four separate occasions: (A) orally administered metformin (1 g), (B) intravenously administered metformin (0.5 g), (C) five doses of tablet codeine 25 mg; the last dose was administered together with oral metformin (1 g), and (D) five doses of tablet codeine 25 mg; the last dose was administered together with metformin (0.5 g) intravenously. Blood samples were drawn for 24 h after administration of metformin, and for 6 h after administration of codeine and analyzed using liquid chromatography and tandem mass spectrometry. Healthy volunteers genotyped as CYP2D6 normal metabolizers (*1/*1) without known reduced function variants in the OCT1 gene (rs12208357, rs34130495, rs34059508, and rs72552763) were invited. The median absorption fraction of metformin was 0.31 and was not influenced by codeine intake. The median time to maximum concentration (Tmax) after oral intake of metformin was 2 h without, and 3 h with codeine (p = 0.06). The geometric mean ratios of the areas under the plasma concentration time‐curve (AUCs) for morphine and its metabolites M3G and M6G for oral intake of metformin‐to‐no metformin were 1.21, 1.31, and 1.27, respectively, and for i.v. metformin‐to‐no metformin 1.28, 1.34, and 1.30, respectively. Concomitant oral and i.v. metformin increased the plasma levels of morphine, M3G and M6G. These small pharmacokinetic changes may well contribute to an increased risk of early discontinuation of metformin. Hence, a clinically relevant drug‐drug interaction between metformin and codeine seems plausible.